Diversity and composition of cladoceran egg bank in sediments and macrophyte roots from the littoral zone of tropical lakes - Daré, Luana [UNESP]; Henry, Raoul [UNESP]; Perbiche-Neves, Gilmar; Castilho, Maria Carolina A.; Portinho, Jorge L. [UNESP] (Springer Nature, 2024)
There is still a fundamental gap in our knowledge regarding the dormant egg bank in the littoral zone, as much of the existing information stems from studies conducted in the pelagic zone. We investigated cladoceran egg banks attached to macrophyte roots (Eichhornia azurea) and the soil surface collected from the littoral site of four Brazilian lakes. We test the hypothesis that sediment supports egg bank communities that are taxonomically distinct from those in macrophyte roots. We took replicate samples from paired examples of each egg bank and later incubated the diapausing eggs in a hatching experiment. Another aspect of our study involved classifying the egg bank community based on the traditional separation of cladocerans according to their microhabitat (pelagic vs. phytophilous). Results from the study indicated that the number of individuals and taxon richness was higher in the sediment egg banks than in those from the macrophyte roots in two of the lakes studied. The proportions of pelagic and phytophilous hatched varied between sediment and macrophyte roots egg banks within each lake studied. These findings partially supported our hypothesis that sediment contains taxonomically distinct egg bank communities compared to those in macrophyte roots. Our results suggest that the littoral zone, particularly the sediment habitat, may serve as a substrate for a persistent dormant egg bank of some pelagic cladocerans. Further comparative research among different macrophyte species and littoral sediments can help to gain more insights into cladoceran ecology and restoration programs for lakes experiencing environmental impacts.
Keywords: Emergence; Macrophytes; Resting eggs; Zooplankton